PATIENT CARE MANAGERS AND INTEGRATED PROGRESS NOTES DOCUMENTATION IN RELATION TO INTERPROFESSIONAL JOB SATISFACTION: A SYSTEMATIC MIXED STUDIES REVIEW - Nurul Hidayah; Dyah Wiji Puspita Sari; Herry Susanto; Nopi Nur Khasanah (RADJA PUBLIKA, 2026)
Effective interprofessional collaboration is increasingly recognized as a key determinant of patient safety, continuity of care, and healthcare worker satisfaction. Within this context, patient care managers and integrated progress notes documentation may function as important mechanisms for coordinating care across disciplines and supporting interprofessional job satisfaction. However, empirical evidence synthesizing the relationship between care coordination roles, shared documentation practices, and job satisfaction remains limited. This systematic mixed studies review aimed to synthesize evidence on the relationship between patient care managers, integrated progress notes documentation, and interprofessional job satisfaction across healthcare settings. A systematic mixed studies review was conducted using a convergent integrated approach. Studies were identified from major databases and screened according to predefined inclusion criteria focused on care coordination roles, integrated progress notes, and interprofessional job satisfaction. The final synthesis included six studies spanning primary care, acute care, geriatric practice, home healthcare, and interprofessional collaboration platforms. The review found that interprofessional job satisfaction was shaped by four interrelated domains: organisational context, digital documentation design, role clarity, and adaptation over time. Integrated progress notes and collaborative documentation systems facilitated communication, reduced duplication, and improved workflow efficiency when aligned with team needs and organisational support. Conversely, role ambiguity, hierarchical relationships, fragmented systems, and resistance to change weakened collaboration and reduced professional satisfaction. Across the included studies, patient care managers emerged as important coordinators who can strengthen shared documentation, promote team cohesion, and support person-centred care. These findings suggest that sustainable improvements require role clarity, shared accountability, interoperable documentation tools, and interprofessional training to strengthen teamwork and workforce well-being.